The Use of Maqasid al-Sharia in Maritime and National Resilience Context - Jahar, Asep Saepudin; Lubis, Amany B.; Fahri, Muhamad (Al-Risalah, 2021)
This study examines the integration between the paradigm of Islamic law and maritime affairs and national resilience. The maqāṣid al-sharīʻa play a significant role in providing a mechanism and its practical strategies on how maritime affairs and national resilience are to be developed. This study aims at highlighting how Islamic law is integrated with maritime affairs and national resilience in the way they are connected with the spiritual-religious values in their development. The maritime affairs and national resilience are used as the object of analysis in an attempt of integrating Islam and natural and social sciences. The study comes to justify the significant role of Islamic values to be put in maritime affairs and national resilience as the foundation to protect life, assets, and future generation.